High-linearity Gilbert-cell mixer design for cryogenic applications - Altuner, Emre; Ozoguz, Ismail Serdar; Yelten, Mustafa Berke (Springer Science and Business Media LLC, 2022)
A Gilbert-cell mixer is designed for operation in cryogenic conditions (-196 degrees C) using UMC 180 nm CMOS technology. The operating frequency is determined as 5 GHz. The proposed mixer achieves an IIP3 of 12.8 dBm, a 1-dB compression of 2.19 dBm, and a conversion gain of around 4 dB at -196 degrees C. The design performance has been compared with the outcomes acquired at room temperature. It is verified that cryogenic conditions enable higher linearity and lower noise figure that elevates the mixer design performance.